PENGAYAAN MATERI FISIKA : INDUKSI ELEKTROMAGNETIK DI SEKOLAH MENENGAH ATAS - Ramacos Fardela; Zulfi Zulfi; Afdhal Muttaqin; Marzuki Marzuki; Dedi Mardiansyah; Mora Mora; Muldarisnur Muldarisnur; Harmadi Harmadi; Rahmad Rasyid; Dahyunir Dahlan; Elvaswer Elvaswer; Imam Taufiq; Wildian Wildian; Trengginas Eka Putra Sutantyo; Feriska Handayani Irka; Dwi Puryanti; Rani Delvihardini (MONSU'ANI TANO Jurnal Pengabdian Masyarakat, 2023)
The concept of electromagnetic induction is very important in understanding and developing modern electrical technology. Some factors cause students to often find it difficult to understand electromagnetic induction material in school is that this material involves abstract concepts such as magnetic flux, magnetic field changes, and emf. For some students, understanding these concepts may be difficult due to a lack of direct experience or concrete representations. Enrichment of physics material on electromagnetic induction has been implemented at SMA N 1 Gunung Talang. This service activity aims to improve students' understanding of the basic concepts of Electromagnetic Induction in Class XII. This service consists of three stages including: preparation, implementation and evaluation. The evaluation of this activity was carried out by comparing the pre-test results before enrichment and the post-test scores of students after being given enrichment material by the lecturer (service team). The results obtained show an increase in student knowledge towards understanding the concept of electromagnetic induction. This service activity can be an effort for school and university cooperation to support student success in understanding physics concepts that are considered complicated